WEER EN KLIMAAT AS OMGEWINGSFAKTORE IN DIE MILITÊRE SITUASIE - Tanred, P. (Scientia Militaria - South African Journal of Military Studies, 2012)
Atmospheric conditions must be taken into account in the strategic and tactial planning of militaryoperations since they can impose decided limitations and can drastically affect the capacityof both soldier and weaponry. Alexander the Great employed meteorological advisers in his army. Napoleon suffered through adverse weather conditions on his Russian campaign and in the Waterloo ’mud bath’. During World War II weather conditions were usually taken into careful consideration in planning. The writer shows to what extent the type of climate governs the mode of warfare, how climatic knowledge is vital to logistics planning, and how climate contributes greatly to the psychological well-being of the soldier.